Impact of DNA extraction methods on the observed microbial communities from the intestinal flora of the penaeid shrimp Litopenaeus vannamei. Issue 9 (10th May 2019) - Jiang, Boyun; Sun, Jingfeng; Lv, Aijun; Hu, Xiucai; Shi, Hongyue; Sung, YeongYik; Wang, Qingkui; Wang, Yang
ABSTRACT: Two DNA extraction methods, the Zirmil-beating cell disruption method (ZBC) and the QIAamp fast DNA stool mini kit (QIA), were used to extract DNA from the intestinal flora of the penaeid shrimp Litopenaeus vannamei, and their microbial communities were analyzed using 16S rDNA high-throughput sequencing. Results were obtained in terms of the number of reads, alpha diversity indexes, beta diversity indexes and taxonomic composition. The alpha diversity indexes of the community, according to the ZBC method, were higher than those according to the QIA method. Furthermore, results from the three samples using the ZBC method were less consistent than those where the QIA method was used. Further, using the latter method led to substantive clustering. It is suggested that the QIA method is more stable and repeatable than the ZBC method. Although the two extraction methods shared the major abundant microflora based on 16S rDNA high-throughput sequencing, bias associated with diversity analysis indexes and certain species was observed. Abstract : Intestinal microbiota of Litopenaeus vannamei was characterized using two DNA extraction methods and high-throughput sequencing.